Predicting outcomes of hematological malignancy patients admitted to critical care - Tridente, Ascanio; Dempsey, Nina C.; Khalifa, Mai; Goddard, Jack; Shuker, Katy; Hall, Joni; Sorour, Youssef; Wright, Josh; Webber, Stephen; Mills, Gary H.; Snowden, John A. (Frontiers in Hematology, 2023)
Background: Critical care (CC) admission has traditionally been viewed as likely to result in a poor outcome for hematological malignancy (HM) patients. Such a view can have implications for decisions surrounding CC admission. Recent studies have challenged this poor prognostication, however, there still remains limited data to support CC admission and escalation decisions and to elucidate risk factors which independently predict short- and longer-term survival outcomes. Methods: We retrospectively analyzed a large cohort of adult HM patients (n=437) admitted to CC over a sixteen-year period, with the specific aim of identifying risk factors present at CC unit admission that could help to predict outcome. We assessed all-cause mortality at CC discharge (CC mortality, primary outcome) and at further time points (hospital discharge and 12-months post-discharge from CC). Single variable and multivariate analyses were performed to identify independent predictors of outcome. Results: CC unit and hospital mortality rates were 33.4% (146 patients) and 46.2% (202 patients) respectively. At six-month and one-year follow-up, mortality increased to 59.5% and 67.9% respectively. At single variable adjusted regression analysis, eight factors were associated with CC mortality: APACHE II score, the number of organs supported, requirement for continuous renal replacement therapy (CRRT), cardiovascular support, or respiratory support (invasive and non-invasive), the ratio between arterial partial pressure of oxygen (PaO2) and the inspired oxygen concentration (FiO2) (P/F ratio) on CC admission, and the lowest P/F ratio during CC admission. However, only three factors showed independent predictive capacity for CC outcome at multivariate logistic regression analysis; APACHE II score on admission, requirement for ventilation and lowest P/F ratio. Conclusion: One third of HM patients admitted to CC died on the unit and, following admission to CC, approximately one-third of HM patients survived over 1 year. Our data show that, while a diagnosis of HM should not preclude admission of patients who might otherwise benefit from CC support, the prognosis of those with a high APACHE II score upon admission, or those requiring IMV remains poor, despite considerable advances in IMV techniques.